Positive electrode material, preparation method thereof and all-solid-state battery
By synthesizing the transition layer and electrolyte cladding layer in situ on the surface of the positive electrode active material, the problem of poor interfacial compatibility of sulfide solid electrolyte under high pressure is solved, the lithium ion transmission efficiency and battery stability are improved, and the circulation performance is achieved and electrochemical window.
Patent Information
- Application Number
- CN202411199720.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-03
AI Technical Summary
The sulfide solid electrolyte has low ion transmission efficiency on the interface of high-voltage positive electrode materials and poor interface compatibility, resulting in attenuation of battery performance and narrow electrochemical windows that cannot support high voltage operation.
The transition layer and electrolyte cladding layer are synthesized in situ on the surface of the positive electrode active material, and annealed by mixing NbM5 and/or TaM5 with the positive electrode active material, or after dissolving with the positive electrode active material using R(NO3)3 or R(NO3)4 with the positive electrode active material. Evaporate and annealing to form a transition layer of spinel phase and an electrolyte cladding layer of LiNbOM4 or LiTaOM4 to solve the problem of lattice mismatch and suppress high-pressure oxygen release.
The effective bonding of the transition layer and the electrolyte cladding layer improves the lithium ion transmission efficiency, reduces side reactions, and improves the stability and cycling performance of the battery under high voltage.
Smart Images

Figure CN119252875A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials for all-solid-state batteries, and in particular to a positive electrode material and a preparation method thereof, and an all-solid-state battery. Background Art
[0002] As one of the alternatives to conventional lithium-ion batteries, solid-state lithium batteries have attracted much attention due to their high safety, wide operating temperature range and simple and feasible battery pack design. Solid electrolyte materials are the core of solid-state lithium batteries and largely determine the various performance parameters of solid-state lithium batteries. Among various solid electrolyte materials, sulfide systems have high ionic conductivity and high ductility, so they are considered to be one of the most promising systems. At present, in the research of sulfide-based solid-state lithium batteries, people have made significant progress in improving electrolyte ion conductivity, surface stability and the development of high-energy density cathode materials. However, as far as sulfide solid electrolytes are concerned, there are still several major challenges: 1) The ionic conductivity is still low. Although sulfide solid electrolytes have high ionic conductivity, the ion transport efficiency at the interface of high-voltage cathode materials may be limited. This increase in interfacial resistance will affect the charge and discharge rate and efficiency of the battery; 2) The interface compatibility between sulfide solid electrolytes and high-voltage cathode materials is poor, and side reactions are prone to occur, leading to electrolyte decomposition and destruction of the cathode material structure. This interfacial instability accelerates the degradation of battery performance, especially under high voltage operating conditions; 3) The electrochemical window of sulfide solid electrolytes is narrow, usually below 4.0V, which limits its compatibility with high voltage cathode materials. In high voltage lithium-ion batteries, cathode materials need to operate at higher voltages to increase energy density, and sulfide solid electrolytes cannot provide sufficient voltage windows to support such operation.
[0003] CN116741935A discloses an electrolyte-coated positive electrode material and a preparation method thereof, wherein the electrolyte-coated positive electrode material comprises a positive electrode active material and a halogen oxide electrolyte coated on the surface thereof; the halogen oxide electrolyte comprises LiNbOX4 and / or LiTaOX4, wherein X comprises any one of F, Cl, Br or I. The electrolyte-coated positive electrode material improves the interface contact between the active material and the electrolyte, significantly reduces the interface impedance, and increases the lithium ion diffusion rate. The cycle performance and rate performance of the lithium battery prepared by using the electrolyte-coated positive electrode material are significantly improved.
[0004] However, the solid electrolyte material used as a coating layer provided by the above technical solution cannot be effectively coated on the surface of the positive electrode material by bonding, and there is a lattice mismatch; in addition, this method cannot effectively reduce the presence of residual alkali on the surface of high-nickel and / or lithium-rich positive electrodes, and cannot effectively improve the ionic conductivity and positive electrode oxygen release under high voltage.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a positive electrode material and a preparation method thereof and an all-solid-state battery, so as to solve the problems of lattice mismatch and oxygen release under high voltage in the existing positive electrode materials.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0008] A first aspect of the present invention provides a method for preparing a positive electrode material, the method comprising the following steps:
[0009] After mixing NbM5 and / or TaM5 with the positive electrode active material, a first annealing treatment is performed, and a transition layer and an electrolyte coating layer are sequentially synthesized in situ on the surface of the positive electrode active material using residual alkali on the surface of the positive electrode active material to obtain the positive electrode material;
[0010] Or, R(NO3)3 or R(NO3)4 and a positive electrode active material are dissolved in an organic solvent, the organic solvent is evaporated, the product obtained after evaporation of the organic solvent is subjected to a second annealing treatment in air, and a transition layer and an electrolyte coating layer are sequentially synthesized in situ on the surface of the positive electrode active material using residual alkali on the surface of the positive electrode active material to obtain the positive electrode material;
[0011] Wherein, M is selected from any one of F, Cl, Br, and I, R is selected from one of Ce, La, and Zr, and the residual alkali on the surface of the positive electrode active material includes lithium carbonate or lithium oxide.
[0012] Preferably, the mass ratio of the NbM5 and / or TaM5 to the positive active electrode material is 0.1-20:100;
[0013] The mass ratio of R(NO3)3 or R(NO3)4 to the positive electrode active material is 0.1-20:100.
[0014] Preferably, the positive electrode active material is selected from any one of ternary materials, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium-rich positive electrode active materials, or a combination of at least two thereof.
[0015] Preferably, the temperature of the first annealing treatment is 100°C-500°C, and the time is 1-12h;
[0016] The temperature of the second annealing treatment is 50° C.-200° C., and the time is 1-12 hours.
[0017] Preferably, the mixing is ball milling mixing or grinding mixing.
[0018] A second aspect of the present invention provides a positive electrode material, wherein the positive electrode material is prepared by the above-mentioned preparation method;
[0019] The positive electrode material comprises a positive electrode active material and a transition layer and an electrolyte coating layer which are sequentially synthesized in situ on the surface of the positive electrode active material;
[0020] Wherein, the transition layer has a spinel phase, the electrolyte coating layer includes LiNbOM4 and / or LiTaOM4, M is selected from any one of F, Cl, Br, I, or the electrolyte coating layer includes LiRO2, and R is selected from one of Ce, La, and Zr.
[0021] According to a third aspect of the present invention, a positive electrode composite material is provided, wherein the positive electrode composite material comprises the positive electrode material mentioned above.
[0022] Preferably, the positive electrode composite material comprises a positive electrode material, a solid electrolyte and a conductive agent;
[0023] The solid electrolyte includes Li6PS5Cl, Li7P2Si8, Li3InCl6, Li2ZrCl6, Li 5.7 PS 4.7 Cl 1.3 , Li 5.4 PS 4.4 Cl 1.6 One or more of;
[0024] The conductive agent includes one or more of VCGF, Super P, acetylene black, KS-6, CNT, graphene, and VGCF.
[0025] Preferably, the mass ratio of the positive electrode material, the solid electrolyte and the conductive agent is (50-80):(20-50):(0.1-5).
[0026] A fourth aspect of the present invention provides an all-solid-state battery, comprising the above-mentioned positive electrode material or the above-mentioned positive electrode composite material.
[0027] Beneficial effects:
[0028] The present invention discloses a positive electrode material, a preparation method thereof and an all-solid-state battery. The present invention utilizes residual alkali on the surface of the positive electrode active material to directly synthesize a transition layer and an electrolyte coating layer in situ on the surface of the positive electrode active material in a one-step method, effectively bonding the transition layer, the electrolyte coating layer and the positive electrode active material, and solving the problem of lattice mismatch; in addition, due to the consumption of residual alkali on the surface of the positive electrode active material, a transition layer with an intermediate phase is induced to form, oxygen vacancies are increased, and the problem of high-pressure oxygen release of the positive electrode material is effectively suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 TEM image of the positive electrode material prepared in Example 1;
[0030] Figure 2 The long cycle performance of the all-solid-state batteries prepared in Example 1 and Comparative Example 1 and the morphology of the electrode materials after the cycle;
[0031] Figure 3 XPS graphs of the positive electrode materials prepared in Example 1 and Comparative Example 1;
[0032] Figure 4 The charge and discharge curves of the all-solid-state batteries prepared in Example 1 and Comparative Example 1;
[0033] Figure 5 The EIS graphs of all-solid-state batteries prepared in Example 1, Example 2, Example 3 and Comparative Example 1 at room temperature;
[0034] Figure 6 This is a shelf EIS graph of the all-solid-state battery prepared in comparative example 1 of example 1 at full charge of 4.8V;
[0035] Figure 7 The rate performance curve diagram of the all-solid-state batteries prepared in Examples 5-7 and Comparative Example 1. DETAILED DESCRIPTION
[0036] The present invention provides a positive electrode material and a preparation method thereof and an all-solid-state battery. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0037] An embodiment of the present invention provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0038] After mixing NbM5 and / or TaM5 with the positive electrode active material, a first annealing treatment is performed, and a transition layer and an electrolyte coating layer are sequentially synthesized in situ on the surface of the positive electrode active material using residual alkali on the surface of the positive electrode active material to obtain the positive electrode material;
[0039] Or, R(NO3)3 or R(NO3)4 and a positive electrode active material are dissolved in an organic solvent, the organic solvent is evaporated, the product obtained after evaporation of the organic solvent is subjected to a second annealing treatment in air, and a transition layer and an electrolyte coating layer are sequentially synthesized in situ on the surface of the positive electrode active material using residual alkali on the surface of the positive electrode active material to obtain the positive electrode material;
[0040] Wherein, M is selected from any one of F, Cl, Br, and I, R is selected from one of Ce, La, and Zr, and the residual alkali on the surface of the positive electrode active material includes lithium carbonate or lithium oxide.
[0041] Under high temperature calcination, the present invention utilizes the residual alkali (lithium carbonate and / or lithium hydroxide) on the surface of the positive electrode to react with the precursor material NbM5 and / or TaM 5, Ce(NO3)3 and / or La(NO3)3 and / or Zr(NO3)4 react, and the reaction products are LiNbOM4 and / or LiTaOM4 and / or LiLaO2 and / or Li2ZrO3. The transition layer and the electrolyte coating layer are directly synthesized in situ on the surface of the positive electrode active material in one step, which effectively bonds the transition layer, the electrolyte coating layer and the positive electrode active material to solve the problem of lattice mismatch. In addition, due to the consumption of residual alkali on the surface of the positive electrode active material, a transition layer with an intermediate phase is induced to form, which increases oxygen vacancies and effectively suppresses the problem of high-pressure oxygen release from the positive electrode material.
[0042] In addition, the electrolyte coating layer can effectively reduce the corrosion of the sulfide electrolyte on the high-voltage positive electrode material, thereby reducing the side reactions between the high-voltage positive electrode material and the sulfide electrolyte, and also help to improve the stability of the high-voltage positive electrode material during the cycle.
[0043] In some embodiments, the mass ratio of the NbM5 and / or TaM5 to the positive electrode active material is 0.1-20:100; the mass ratio of the R(NO3)3 or R(NO3)4 to the positive electrode active material is 0.1-20:100.
[0044] Among them, NbM5, TaM5, Ce(NO3)3, La(NO3)3, Zr(NO3)4, R(NO3)3, and R(NO3)4 are all precursor materials. The mass ratio of NbM5 and / or TaM5 to the positive electrode active material can be 0.1:100, 0.5:100, 1:100, 2:100, 5:100, 10:100, 15:100, 20:100, and the mass ratio of R(NO3)3 or R(NO3)4 to the positive electrode active material can be 0.1:100, 0.5:100, 1:100, 2:100, 5:100, 10:100, 15:100, 20:100.
[0045] If the mass percentage of the precursor material is too low, the residual alkali on the surface of the positive electrode active material cannot be consumed, and the transition layer and the electrolyte coating layer cannot be effectively formed on the surface of the positive electrode active material; if the mass percentage is too high, the residual alkali on the surface of the positive electrode active material cannot meet the consumption of the precursor material, and some precursor materials that have not reacted in situ will exist, resulting in increased battery polarization.
[0046] In some preferred embodiments, the mass ratio of the NbM5 and / or TaM5 to the positive electrode active material is (0.1-5):100, and the mass ratio of the R(NO3)3 or R(NO3)4 to the positive electrode active material is (0.1-5):100.
[0047] In some embodiments, the positive electrode active material is selected from any one of ternary materials, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and a lithium-rich positive electrode active material, or a combination of at least two thereof.
[0048] In some embodiments, the ternary material includes ternary material NCA and / or ternary material NCM.
[0049] In some embodiments, the ternary material includes one or more of NCM622, NCM811, Ni83, and Ni90.
[0050] In some embodiments, the lithium-rich positive electrode active material includes one or more of a lithium-rich manganese-based, a lithium-rich nickel-manganese-based, and a lithium-rich nickel-cobalt-manganese-based positive electrode active material.
[0051] In some embodiments, the first annealing treatment is performed at a temperature of 100°C-500°C for 1-12 hours; the second annealing treatment is performed at a temperature of 50°C-200°C for 1-12 hours.
[0052] The temperature of the first annealing treatment may be 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, and the time may be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h. The temperature of the second annealing treatment may be 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, and the time may be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h.
[0053] If the annealing temperature is too low, the residual alkali on the surface of the positive electrode active material cannot react with the precursor material, and the transition layer and the electrolyte coating layer cannot be generated in situ; if the annealing temperature is too high, the lattice structure of the positive electrode active material and the in-situ coating layer will be destroyed, causing the battery performance to deteriorate rapidly; in the appropriate temperature range, the residual alkali on the surface will be consumed in an appropriate amount, and a coating layer will be generated in situ.
[0054] In some preferred embodiments, the first annealing treatment is performed at a temperature of 150° C. for 5 hours, and the second annealing treatment is performed at a temperature of 150° C. for 5 hours.
[0055] In some embodiments, the annealing process is performed in an argon atmosphere, a nitrogen atmosphere, a hydrogen-argon mixed gas atmosphere, or a vacuum.
[0056] In some embodiments, the mixing is ball milling mixing or grinding mixing.
[0057] In some embodiments, the positive electrode material is prepared by any one of an agate plate grinding annealing method and a ball milling annealing method.
[0058] The agate dish grinding annealing method has a simple process and low cost, while the ball milling annealing method requires more raw materials, one for small batches and the other for large batches. The vapor deposition method and vacuum evaporation method have high requirements for equipment, high cost and energy consumption, and limited single output, which is not conducive to large-scale expansion.
[0059] In some embodiments, the grinding and mixing is performed in a glove box, and the grinding tool for the grinding and mixing is an agate dish.
[0060] In some embodiments, the ball milling mixing is performed in a ball mill.
[0061] In some embodiments, the ball milling beads used in the ball milling mixture are zirconium oxide ball milling beads, and the diameter of the ball milling beads is 4-10 mm.
[0062] In some embodiments, the ball-to-material ratio of the ball-milling mixture is (20-50):1, for example, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, etc.
[0063] In some embodiments, the ball milling mixing speed is 50-1000rpm, for example 50rpm, 100rpm, 150rpm, 200rpm, 300rpm, 400rpm, 500rpm, 550rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, and the time is 2-72h, for example 1h, 2h, 5h, 10h, 20h, 30h, 40h, 50h, 60h, 70h or 72h.
[0064] An embodiment of the present invention provides a positive electrode material, wherein the positive electrode material is prepared by the above-mentioned preparation method;
[0065] The positive electrode material comprises a positive electrode active material and a transition layer and an electrolyte coating layer which are sequentially synthesized in situ on the surface of the positive electrode active material;
[0066] Among them, the transition layer includes a lithium manganate structure and / or a rock salt phase structure of a spinel structure formed after the lithium in the positive electrode material reacts with the modified material, which effectively suppresses the problem of high-voltage oxygen release of the positive electrode material, and the spinel structure has a high lattice matching degree with the internal layered structure, which promotes the transmission of lithium ions; the electrolyte coating layer includes LiNbOM4 and / or LiTaOM4, M is selected from any one of F, Cl, Br, I, or the electrolyte coating layer includes LiRO2, R is selected from one of Ce, La, Zr.
[0067] An embodiment of the present invention provides a positive electrode composite material, wherein the positive electrode composite material includes the positive electrode material mentioned above.
[0068] In some embodiments, the cathode composite material includes a cathode material, a solid electrolyte, and a conductive agent;
[0069] The solid electrolyte includes Li6PS5Cl, Li7P2Si8, Li3InCl6, Li2ZrCl6, Li 5.7 PS 4.7 Cl 1.3 , Li 5.4 PS 4.4 Cl 1.6 One or more of;
[0070] The conductive agent includes one or more of VCGF, Super P, acetylene black, KS-6, CNT, graphene, and VGCF.
[0071] In some embodiments, the mass ratio of the positive electrode material, the solid electrolyte and the conductive agent is (50-80):(20-50):(0.1-5), for example, 70:30:1, 80:20:1, etc.
[0072] An embodiment of the present invention provides an all-solid-state battery, which includes the above-mentioned positive electrode material or the above-mentioned positive electrode composite material.
[0073] In some embodiments, the all-solid-state battery includes a solid electrolyte, the above-mentioned positive electrode composite material and a negative electrode material.
[0074] In some embodiments, the all-solid-state battery is prepared by the following method: adding a solid electrolyte to a model battery and performing a first tableting; adding the positive electrode composite material as described above to one side of the model battery and performing a second tableting; attaching the negative electrode material to the other side of the model battery, performing a third tableting, and assembling to obtain the all-solid-state battery.
[0075] In some embodiments, the first tableting process is performed at a pressure of 100-500 MPa and for a time of 1-10 min.
[0076] In some embodiments, the second tableting process is performed at a pressure of 300-800 MPa and for a time of 1-10 min.
[0077] In some embodiments, the third tableting process is performed at a pressure of 1-100 MPa and for a time of 1-10 min.
[0078] In some embodiments, the negative electrode material includes any one of a lithium metal negative electrode material, a silicon negative electrode material, a silver-carbon negative electrode material, or a lithium alloy negative electrode material, or a combination of at least two thereof.
[0079] In some embodiments, the lithium alloy negative electrode material includes any one of a lithium indium alloy sheet, a lithium magnesium alloy sheet, or a lithium aluminum alloy sheet, or a combination of at least two thereof.
[0080] In some embodiments, the assembled pressure is ≥ 50 kPa.
[0081] In some embodiments, the preparation of the all-solid-state battery is completed in an argon glove box.
[0082] In some embodiments, the preparation of the all-solid-state battery is carried out at room temperature.
[0083] In some embodiments, the mass of the solid electrolyte is 60-150 mg, the mass of the positive electrode composite material is 5-40 mg, and the diameter of the lithium-indium alloy sheet is 8-10 mm and the thickness is 0.1-0.5 mm.
[0084] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0085] Example 1
[0086] The preparation of all-solid-state batteries includes the following steps:
[0087] Preparation of positive electrode composite material: 1g of lithium-rich manganese-based active material (denoted as LLO) and 1mg of precursor material NbF5 were ground and mixed according to (mass ratio of 0.1:100), transferred to a high-temperature furnace, heated to 120°C at a rate of 3°C / min in an inert atmosphere and annealed at this temperature for 5 hours; after completion, the product was cooled to room temperature in an inert atmosphere to obtain a positive electrode material powder, denoted as C-LLO; C-LLO, solid electrolyte L6PS5Cl and conductive agent (VGCF) were mixed in a mass percentage of 70:25:5 to obtain a positive electrode composite material.
[0088] Preparation of all-solid-state batteries: Sulfide solid electrolyte powder L 7-x PS 6-x Cl x (0≤x≤3) is added to a tablet pressing mold and maintained at a pressure of 500 MPa for 1 min to press the sulfide solid electrolyte powder into an electrolyte sheet. The above-prepared positive electrode composite material is evenly sprinkled on one side of the electrolyte sheet and maintained at a pressure of 500 MPa for 1 min. A lithium-indium alloy sheet is added to the other side of the electrolyte sheet and maintained at a pressure of 20 MPa for 1 min to assemble into an all-solid-state battery.
[0089] Example 2
[0090] Preparation of an all-solid-state battery. The preparation steps of the all-solid-state battery in this embodiment are basically the same as those in the above-mentioned embodiment 1, with the only difference being that the mass of the lithium-rich manganese-based active material (denoted as LLO) is 1 g, the mass of the precursor material NbF5 is 5 mg, and the mass ratio of the precursor material to the lithium-rich manganese-based active material is 0.5:100.
[0091] Example 3
[0092] Preparation of an all-solid-state battery. The preparation steps of the all-solid-state battery in this embodiment are basically the same as those in the above-mentioned embodiment 1, with the only difference being that the mass of the lithium-rich manganese-based active material (denoted as LLO) is 1 g, the mass of the precursor material NbF5 is 10 mg, and the mass ratio of the precursor material to the lithium-rich manganese-based active material is 1:100.
[0093] Example 4
[0094] Preparation of an all-solid-state battery. The preparation steps of the all-solid-state battery in this embodiment are basically the same as those in the above-mentioned embodiment 1, with the only difference being that the mass of the lithium-rich manganese-based active material (denoted as LLO) is 1 g, the mass of the precursor material NbF5 is 50 mg, and the mass ratio of the precursor material to the lithium-rich manganese-based active material is 5:100.
[0095] Example 5
[0096] Preparation of an all-solid-state battery. The preparation steps of the all-solid-state battery in this embodiment are basically the same as those in the above-mentioned embodiment 1, except that the positive electrode material powder is prepared. The positive electrode material powder in this embodiment is prepared as follows:
[0097] 1 g of lithium-rich manganese-based active material (denoted as LLO) and 5 mg of precursor material Ce(NO3)3 were dissolved in 500 mL of anhydrous ethanol (mass ratio of 0.5:100). The product was obtained after heating, stirring and evaporation with a magnetic stirrer. The product was annealed at 500°C in air for 5 h to obtain a positive electrode material powder, denoted as C-LLO.
[0098] Example 6
[0099] Preparation of an all-solid-state battery. The preparation steps of the all-solid-state battery in this embodiment are basically the same as those in the above-mentioned embodiment 1, except that the positive electrode material powder is prepared. The positive electrode material powder in this embodiment is prepared as follows:
[0100] 1 g of lithium-rich manganese-based active material (denoted as LLO) and 5 mg of precursor material La(NO3)3 were dissolved in 500 mL of anhydrous ethanol (mass ratio of 0.5:100). The product was obtained after heating, stirring and evaporation with a magnetic stirrer. The product was annealed at 500°C in air for 5 h to obtain a positive electrode material powder, denoted as C-LLO.
[0101] Example 7
[0102] Preparation of an all-solid-state battery. The preparation steps of the all-solid-state battery in this embodiment are basically the same as those in the above-mentioned embodiment 1, except that the positive electrode material powder is prepared. The positive electrode material powder in this embodiment is prepared as follows:
[0103] 1 g of lithium-rich manganese-based active material (denoted as LLO) and 5 mg of precursor material Zr(NO3)4 were dissolved in 500 mL of anhydrous ethanol (mass ratio of 0.5:100). The product was obtained after heating, stirring and evaporation with a magnetic stirrer. The product was annealed at 500°C in air for 5 h to obtain a positive electrode material powder, denoted as C-LLO.
[0104] Comparative Example 1
[0105] Preparation of an all-solid-state battery. The preparation steps of the all-solid-state battery in this comparative example are basically the same as those in the above-mentioned Example 1, with the only difference being that the lithium-rich manganese-based active material is directly mixed with the sulfide solid electrolyte powder and the conductive agent to prepare the all-solid-state battery.
[0106] The all-solid-state batteries prepared in the examples and comparative examples were tested as follows:
[0107] First cycle charge and discharge curve: fix the charge and discharge rate to 0.1C, and calculate the coulombic efficiency.
[0108] Battery cycle performance: The battery was subjected to a cycle charge and discharge test at a rate of 1C, and the initial efficiency and capacity retention rate after 300 cycles were measured.
[0109] Shelf impedance: The shelf impedance is tested at full charge 4.8V.
[0110] Test voltage is 2-4.8V, vs.Li + / Li.
[0111] The test results are shown in Table 1.
[0112] Table 1
[0113]
[0114] According to the test results in Table 1, compared with Examples 1-7, if the positive electrode active material is not in-situ coated (Comparative Example 1), the first efficiency and capacity retention rate are lower. Among them, Example 3, which is in-situ coated with 1% NbF5 precursor material, has the best effect, with an first efficiency of 83.6%, and a capacity retention rate of 83% after 300 cycles.
[0115] Figure 1 TEM image of the positive electrode material prepared in Example 1: Figure 1 It shows that a uniform electrolyte coating layer is formed on the surface of the positive electrode active material, and an intermediate transition layer is also generated. The electrolyte coating layer can effectively inhibit the side reaction between the positive electrode active material and the sulfide electrolyte.
[0116] Figure 2 The long cycle performance of the all-solid-state batteries prepared in Example 1 and Comparative Example 1 and the morphology of the electrode materials after the cycle: Figure 2 It shows that after the precursor material is in situ coated, the long cycle retention rate at 1C is greatly improved, and the inset in the figure is the SEM image of the positive electrode material after cycling. It can be clearly found that the in situ coating can effectively inhibit the side reactions of the positive electrode active material and the sulfide electrolyte, so that the positive electrode particles remain intact after the in situ coated material is cycled.
[0117] Figure 3 The XPS graphs of the positive electrode materials in Example 1 and Comparative Example 1 are as follows: Figure 3 It shows that after in-situ coating of the precursor material, the oxygen vacancy content in the positive electrode active material increases, and the oxygen vacancies can effectively inhibit the precipitation of lattice oxygen during the charging and discharging process, thereby effectively improving the coulombic efficiency.
[0118] Figure 4 The charge and discharge curves of the all-solid-state batteries prepared in Example 1 and Comparative Example 1 are as follows: Figure 4 It shows that after in-situ coating of the precursor material, the first-cycle coulombic efficiency is greatly improved, and the discharge specific capacity at 0.1C is also greatly improved.
[0119] Figure 5 The EIS graphs of all-solid-state batteries prepared in Example 1, Example 2, Example 3 and Comparative Example 1 at room temperature are as follows: Figure 5 It shows that after in-situ coating of the precursor material, the impedance of the full battery is significantly reduced because the formed in-situ coating layer has a higher ionic conductivity.
[0120] Figure 6 This is the EIS graph of the all-solid-state battery prepared in Example 1 and Comparative Example 1 at 4.8V full charge: Figure 6It shows that after the precursor material is in-situ coated, the full-charge shelf impedance remains basically unchanged, indicating that after in-situ coating and the formation of an intermediate phase transition layer, its high-voltage stability is extremely good.
[0121] Figure 7 The rate performance curves of all-solid-state batteries prepared in Examples 5-7 and Comparative Example 1 are as follows: Figure 7 It shows that after in-situ coating with oxides of La, Ce, and Zr (such as LiCeO2, LiLaO2, and LiZrO2), the rate performance is improved, indicating that after in-situ coating and the formation of an intermediate phase transition layer, the ionic conductivity is improved.
[0122] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The preparation method comprises the following steps: After mixing NbM5 and / or TaM5 with the positive electrode active material, a first annealing treatment is performed, and a transition layer and an electrolyte coating layer are sequentially synthesized in situ on the surface of the positive electrode active material using residual alkali on the surface of the positive electrode active material to obtain the positive electrode material; Or, R(NO3)3 or R(NO3)4 and a positive electrode active material are dissolved in an organic solvent, the organic solvent is evaporated, the product obtained after evaporation of the organic solvent is subjected to a second annealing treatment in air, and a transition layer and an electrolyte coating layer are sequentially synthesized in situ on the surface of the positive electrode active material using residual alkali on the surface of the positive electrode active material to obtain the positive electrode material; Wherein, M is selected from any one of F, Cl, Br, and I, R is selected from one of Ce, La, and Zr, and the residual alkali on the surface of the positive electrode active material includes lithium carbonate or lithium oxide.
2. The method for preparing the positive electrode material according to claim 1, characterized in that: The mass ratio of the NbM5 and / or TaM5 to the positive active electrode material is 0.1-20:100; The mass ratio of R(NO3)3 or R(NO3)4 to the positive electrode active material is 0.1-20:
100.
3. The method for preparing the positive electrode material according to claim 1, characterized in that: The positive electrode active material is selected from any one of ternary materials, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium-rich positive electrode active materials, or a combination of at least two thereof.
4. The method for preparing the positive electrode material according to claim 1, characterized in that: The temperature of the first annealing treatment is 100°C-500°C, and the time is 1-12h; The temperature of the second annealing treatment is 50° C.-200° C., and the time is 1-12 hours.
5. The method for preparing the positive electrode material according to claim 1, characterized in that: The mixing is ball milling mixing or grinding mixing.
6. A positive electrode material, characterized in that The positive electrode material is prepared by the preparation method according to any one of claims 1 to 5; The positive electrode material comprises a positive electrode active material and a transition layer and an electrolyte coating layer which are sequentially synthesized in situ on the surface of the positive electrode active material; Wherein, the transition layer has a spinel phase, the electrolyte coating layer includes LiNbOM4 and / or LiTaOM4, M is selected from any one of F, Cl, Br, I, or the electrolyte coating layer includes LiRO2, and R is selected from one of Ce, La, and Zr.
7. A positive electrode composite material, characterized in that: The positive electrode composite material comprises the positive electrode material according to claim 6.
8. The positive electrode composite material according to claim 7, characterized in that: The positive electrode composite material comprises a positive electrode material, a solid electrolyte and a conductive agent; The solid electrolyte includes Li6PS5Cl, Li7P2Si8, Li3InCl6, Li2ZrCl6, Li 5.7 PS 4.7 Cl 1.3 , Li 5.4 PS 4.4 Cl 1.6 One or more of; The conductive agent includes one or more of VCGF, Super P, acetylene black, KS-6, CNT, graphene, and VGCF.
9. The positive electrode composite material according to claim 8, characterized in that: The mass ratio of the positive electrode material, the solid electrolyte and the conductive agent is (50-80):(20-50):(0.1-5).
10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the positive electrode material according to claim 6 or the positive electrode composite material according to any one of claims 7 to 9.
Citation Information
Patent Citations
Coated ternary positive electrode material and preparation method and application thereof
CN110970604A
Metal compound coated ternary positive electrode material and preparation method thereof
CN112002901A
Electrolyte-coated positive electrode material as well as preparation method and application thereof
CN116741935A
Modified positive electrode material, preparation method thereof and all-solid-state lithium ion battery
CN118039833A